THE MICROSCOPIC MODELLING OF TRAFFIC ON CHOSEN PART OF COMMERCIAL AREA IN CITY OF ZILINA (Perner's Contacts, 2012)
The paper describes the method of microsco pic modeling of chosen part in city of Zilina.  It  is  focused  on  evaluation  of  variants  of transport  infrastrucutre  in  the future.
Keywords: microscopic transport modeling, transport infrastructure, transport model